Hermeneutika Al-Qur’an Untuk Pembebasan : Telaah Kritis Pemikiran Hassan Hanafi - Ilham B. Saenong (Millah: Journal of Religious Studies, 2004)
No hermeneutics per se, absolute, and universal. Hermeneutics always has a particular dimension and has been  the integral part of  social revolution. The  current heading to a more praxis-oriented is much more tangible in Hassan Hanafi’s thought in hermeneutics. It also differentiated Hanafi from others  contemporary mufassir (hermeneut) as well. A few  Muslim scholars who pay close attention to the notion of  liberation in Islamic teaching. Moreover, taking the risk to work laboriously to elaborate the method of  interpreting al-Qur’an  -  which has something to do with the suffering of  the oppressed groups. The writing has worked on the background, Hanqfi’s position as an eminence Islamic thinker, and his relation to the others contemporary Islamic thinkers, along with a bit of  critical notes.